2017
DOI: 10.13045/acupunct.2017070
|View full text |Cite
|
Sign up to set email alerts
|

MOK, a Pharmacopuncture Medicine, Reduces Inflammatory Response through Inhibiting the Proinflammatory Cytokine Production in LPS-stimulated Mouse Peritoneal Macrophages

Abstract: [Abstract]Objectives : Inthisstudy,weinvestigatedtheanti-inflammatoryandanti-oxidativeeffectsof MOK,apharmacopuncturemedicine,inlipopolysaccharide(LPS)-stimulatedmouseperitoneal macrophages. Methods : PeritonealmacrophageswereisolatedfromICRmice.Primarymacrophageswere treatedwithMOKextract(1.25,2.5,5,10,and20mg/ml)for30minandthenstimulatedwith LPS(1μg/ml)fortheindicatedtimes.CytotoxicitywasmeasuredusingMTTandLDHassays. Nitricoxide(NO)productioninculturesupernatantswasmeasuredusingtheGriessassay. ThemRNAexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The endogenous components of the antioxidant system include enzymes such as SOD, glutathione peroxidase (GSPx), and HO-1 34,35) . We previously reported that the antioxidant effects of MOK extract in LPSstimulated mouse peritoneal macrophages occurred via an increase in the expressions of MnSOD and HO-1 7) . In the present study, the treatment of splenocytes with MOK increased the mRNA expression of MnSOD and HO-1.…”
Section: ⅳ Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The endogenous components of the antioxidant system include enzymes such as SOD, glutathione peroxidase (GSPx), and HO-1 34,35) . We previously reported that the antioxidant effects of MOK extract in LPSstimulated mouse peritoneal macrophages occurred via an increase in the expressions of MnSOD and HO-1 7) . In the present study, the treatment of splenocytes with MOK increased the mRNA expression of MnSOD and HO-1.…”
Section: ⅳ Discussionmentioning
confidence: 96%
“…However, comparisons of the biological activity of MOK with that of single medicines have been rarely reported. We have previously reported the anti-inflammatory and antioxidant effects of MOK extract in activated peritoneal macrophages 7) .…”
Section: ⅳ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOK is a polyherbal medicine for the immuno-pharmacopuncture therapy and it is clinically used to treat the meridian of fire in nature and symptoms related to heart disease, such as fright palpitations, fearful throbbing, sleep disorders, angina pectoris, and thyroid diseases, such as hyperthyroidism, hypothyroidism, thyroid hypertrophy, and benign thyroid nodules [ 14 ]. Recently, the anti-inflammatory and antioxidative effects of MOK have been reported [ 15 ], but little scientific evidence of MOK has been found. Therefore, we investigated the therapeutic effects of MOK pharmacopuncture in an LT4-induced hyperthyroidism rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacopuncture with MOK is used for the treatment of patients with thyroid diseases such as hypothyroidism, hyperthyroidism, and heart issues. Although MOK is commonly used in Korean clinics and some studies have reported its anti-inflammatory and antioxidative effects [ 15 ], it has little scientific evidence. Therefore, in this study, we investigated the effects of the pharmacopuncture with MOK on thyroid dysfunction in L-thyroxin (LT4)-induced hyperthyroidism rats, and the possible mechanism.…”
Section: Introductionmentioning
confidence: 99%